"EFFECTS OF ELECTROMAGNETIC FIELD ON BIOLOGICAL OBJECTS" PRACTICAL COURSE ONLINE ON MODULAR SYSTEM. - Askar Ergashev Jongoboevich; Abdullo Nabiev Abduvoxidovich; Gulmira Kholmuminova Olim qizi (Genius Journals, 2022)
This article consists of three main parts and a conclusion. This article is published in Samarkand State Medical Institute “The effect of electromagnetic fields on biological objects" devoted to methods of teaching the subject. The first part provides methodological guidelines for the module system, and the second part provides practical course information. In the third part, the module system assesses students' scores on lectures and control tests, mutual questions and answers, independent work and activity in the classroom
Keywords: Electromagnetic field; training in a modular system; practical lesson; independent work